2023
DOI: 10.1038/s41557-023-01244-8
|View full text |Cite
|
Sign up to set email alerts
|

Mass photometric detection and quantification of nanoscale α-synuclein phase separation

Abstract: α-Synuclein (α-Syn) liquid-liquid phase separation (LLPS) leads to irreversible amyloid fibril formation associated with Parkinson's disease pathogenesis. Critical concentrations of α-Syn LLPS are relatively high under physiological solution conditions. Moreover, α-Syn exhibits delayed LLPS kinetics under certain conditions which deviates from the behaviour predicted by classical homogeneous nucleation theory. In the current body of work, using interferometric light scattering (iSCAT), also known as mass photo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 110 publications
(134 reference statements)
5
22
0
Order By: Relevance
“…164 11D,E). 167 They showed that even at dilute concentrations far from the concentrations needed for macroscopic assembly to be observed, these proteins nucleate and form nanoclusters that are kinetically trapped. They were able to explore the role of temperature, pH, molecular crowders, and biochemical modification across a wide range of masses spanning 50−1500 kDA.…”
Section: Part 3: Microfluidic Platforms and Emerging Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…164 11D,E). 167 They showed that even at dilute concentrations far from the concentrations needed for macroscopic assembly to be observed, these proteins nucleate and form nanoclusters that are kinetically trapped. They were able to explore the role of temperature, pH, molecular crowders, and biochemical modification across a wide range of masses spanning 50−1500 kDA.…”
Section: Part 3: Microfluidic Platforms and Emerging Technologiesmentioning
confidence: 99%
“…(C–E) X-ray interferometric scattering microscopy (ISCAT) and mass photometry. Reprinted with permission from ref . Copyright 2023 Springer Nature.…”
Section: Part 3: Microfluidic Platforms and Emerging Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid−liquid phase separation (LLPS) is critical in many physiological processes like the formation of membrane-less organelles and disease-related amyloid fibrils. 37 It is also a key process in the assembly of colloidal and biopolymer systems. During the spinning of natural silk, the precursors are preserved as the LLPS form, forming a condensed phase of protein materials that can further solidify during liquid-to-solid transition.…”
Section: Modular Assembly Into Biomimetic Fiber Materialsmentioning
confidence: 99%
“…Various assembly techniques and inducing molecules have been involved in modular assembly, endowing the bulk material with novel optical, thermodynamic, and physiological features. Liquid–liquid phase separation (LLPS) is critical in many physiological processes like the formation of membrane-less organelles and disease-related amyloid fibrils . It is also a key process in the assembly of colloidal and biopolymer systems.…”
Section: Modular Assembly Into Biomimetic Fiber Materialsmentioning
confidence: 99%